Prediction study of structural, electronic and optical properties of XIn2S4 (X = Hg, Zn) thiospinels under pressure effect - Masood, Yousaf (2014)
First principle calculations are carried out to study the effect of pressure (up to 30 GPa) on physical properties of HgIn2S4 and ZnIn2S4 thiospinels. A number of structural, electronic and optical parameters are calculated, and equations are developed for their prediction at different pressures. Highly effective all electron FP-LAPW+lo method coupled with two different approximations (GGA+U and mBJ-GGA) provides very accurate results. All relationships developed between pressure and structural parameters are in full accordance with the established theory thus validating the approach used in the current study. Computed In-S bond length for ZnIn2S4 matches closely with the experimental value. The band gap values of 0.920 eV (1.851 eV) and 1.68 eV (2.733 eV) are obtained with GGA+U (mBJ-GGA) at 0 GPa for HgIn2S4 and ZnIn 2S4, respectively. Additionally, we have calculated the optical properties, namely, the complex dielectric function, refractive index, extinction coefficient, reflectivity, optical conductivity, absorption coefficient and electron energy loss function under pressure effect for radiation up to 30.0 eV. The first critical point also known as optical's absorption edge calculated with GGA+U (mBJ-GGA) appears at 0.939 eV (1.891 eV) and 1.701 eV (2.981 eV) for HgIn2S4 and ZnIn 2S4, respectively. Variation of the absorption spectrum indicates the prospective use of both compounds for device applications, which can be operated on a wide range of the energy scale. The entire work gives useful results of fundamental importance, which can be utilized for the fabrication of optoelectronic devices.